Implementasi E-Commerce Untuk Meningkatkan Penjualan Industri Rumahan Randang Padang Berbasis Web - Sri Restu Ningsih; Ade Irma Suryani; Arika Juwita Z (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
Randang Padang is a typical food of the Minang people which is very well known, even abroad. Currently Randang Padang Elok does not yet have an online system, because there is no effective marketing media to explain in detail the products available at Randang Padang Elok, and sales transactions are still carried out manually where sales data and product data are recorded manually, into a ledger , so that to make a report the company officer has to manually recapitulate data files. The purpose of this research is to build an e-commerce-based website to make it easier for this home industry to carry out a sales system and product monitoring. This system was created using the System Development Life Cycle (SDLC) with the Waterfall method. Making this system using the PHP programming language and MySQL database. The results of this study can make it easier for Randang Padang Elok to carry out an online sales system, find out order conditions, and expand the marketing area and increase the number of consumers so that product sales information media will be more effective and efficient.